Pepsin like activity in bronchoalveolar lavage fluid is suggestive of gastric aspiration in lung allografts. Issue 10 (29th July 2005) - Ward, C; Forrest, I A; Brownlee, I A; Johnson, G E; Murphy, D M; Pearson, J P; Dark, J H; Corris, P A
Abstract : Background: A biologically plausible link between gastro-oesophageal reflux (GOR), aspiration, and lung allograft dysfunction has been suggested, but there is no systematic evidence indicating the presence of gastric contents in the lung. We have tested the hypothesis that pepsin, as a marker of aspiration, is detectable in bronchoalveolar lavage (BAL) fluid of allograft recipients who had not reported symptoms of GOR. Methods: Standardised 3×60 ml surveillance BAL fluid samples from 13 chronologically sequential stable lung allograft recipients without chronic rejection (10 patients treated with a prophylactic proton pump inhibitor) were studied. Lavage supernatants were assayed by an ELISA based on a monospecific goat antibody for pepsin/pepsinogen. Pepsin levels were compared with those from four normal volunteer controls. Results: Pepsin levels were measurable in all allograft recipients, in keeping with gastric aspiration (median 109 ng/ml (range 35–1375)). In the control group the pepsin levels were below the limit of detection. Treatment with a proton pump inhibitor was not correlated with pepsin levels. There was no correlation between BAL fluid neutrophils and pepsin levels. Conclusion: These data demonstrate lung epithelial lining fluid concentrations of pepsin in lung allograft recipients which are much higher than blood reference levels, with no detectable pepsin in controls. This provides direct evidence of gastric aspiration, which is potentially injurious to the allograft.